2002
DOI: 10.1016/s0531-5131(02)00996-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of AGE–RAGE system in the development of diabetic nephropathy in vivo

Abstract: Vascular complications are what eventually threaten the lives of diabetic patients.Here we show direct in vivo evidence that the interaction between advanced glycation endproducts (AGE), the formation of which is accelerated during prolonged hyperglycemic exposure, and a cell surface receptor for AGE (RAGE) is the major cause of such complications. We created transgenic mice that overexpress human RAGE in vascular cells and crossbred them with another transgenic line which develops insulin-dependent diabetes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…As shown in Figure 4 , the pathway enrichment analysis with ClueGO (a Cytoscape plugin) showed that key targets were mainly assigned to the AGE-RAGE and IL-17 signaling pathway. These pathways played a definite role in oxidative stress, glycolipid metabolism, inflammation, and renal fibrosis [ 38 40 ]. The typical targets of RC are regulated via a lot of pathways, such as DPP4, SOD1, ATK1, TGF- β 1, SphK1, RAGE, MAPK3, IL-6, PTK1, NOX4, TNF- α , and NF- κ B.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4 , the pathway enrichment analysis with ClueGO (a Cytoscape plugin) showed that key targets were mainly assigned to the AGE-RAGE and IL-17 signaling pathway. These pathways played a definite role in oxidative stress, glycolipid metabolism, inflammation, and renal fibrosis [ 38 40 ]. The typical targets of RC are regulated via a lot of pathways, such as DPP4, SOD1, ATK1, TGF- β 1, SphK1, RAGE, MAPK3, IL-6, PTK1, NOX4, TNF- α , and NF- κ B.…”
Section: Resultsmentioning
confidence: 99%
“…Receptors for AGEs were believed to play a critical role in AGEs related biology and the pathology associated with diabetic complications and aging disorders [44][45][46][47]. Some known popular receptors are: the RAGE [48], oligosaccharyl transferase-48 (AGE-R1) [49], galectin-3 (AGE-R3) [50], CD36 [51], and macrophage scavenger receptor types I and II [52].…”
Section: Effects Of Ages In Vivomentioning
confidence: 99%
“…Yamamoto et al [44] created transgenic mice that overexpress human RAGE in vascular cells, and crossbred them with another transgenic line which develops insulin-dependent diabetes early after birth. They found that the resultant double transgenic exhibited accelerated kidney changes compared with single transgenic littermales.…”
Section: Effects Of Ages In Vivomentioning
confidence: 99%